Assessment of Infrastructures Assets Induced by Water Level Fluctuation along the Bengawan Solo River - T. R. Satrya; Ria Asih Aryani Soemitro; M. A. Maulana; D. D. Warnana; R. Soetanto (Journal of Infrastructure & Facility Asset Management, 2019)
The stability of infrastructure along river channel, such as bridges and embankments, is paramount to continuing service and public safety, and therefore, is essential consideration in the design, construction and maintenance. During the design process, infrastructure stability is often assumed to be static, and considered by implementing a safety factor which is produced by an analysis of extreme condition. However, this has failed to consider the variability of natural factors and importantly, the escalating threat of extreme environmental condition, induced by global climate change. This assumption should, therefore, be revisited for developing a more resilient design and maintenance regime. To demonstrate the changing infrastructure stability, an assessment of safety factor of river embankment and bridge foundation as nearby infrastructures along Bengawan Solo River’s channel and estuary is presented. This was undertaken to determine the impact of water level fluctuation during two extreme conditions during dry and rainy seasons in several critical locations. The river characteristics (i.e. morphology, water fluctuations, velocity, and sub-soil characteristics), embankment conditions and bridge pile foundation were investigated in-situ to assess the change of safety factor. The laboratory investigation focused on river and embankment characteristics including the analysis of the drying-wetting conditions. In-situ and laboratory investigations found an extreme condition which the infrastructures are subjected into, where the water level and flow velocity were 3 m and 0.04 - 0.27 m/s during dry season; and 10 m and 0.46 - 0.84 m/s during rainy season. Furthermore, from the analysis, it can be concluded that certain areas in the river do not meet the minimum requirements for bridge foundation and embankment stability.